Implementation Of Financial Recording In UMKM Pulse (Study On Pulse Counters In CV. Mietha Global) - Rena Andriani; Reni Andriana; Achmad Wicaksono (Jurnal Ekonomi, 2024)
The credit counter business is increasingly in demand every year as one of the most profitable businesses, as seen from the advancement of telecommunications technology today. Among the tangible evidence of the sophistication of telecommunications technology is the availability of communication infrastructure through cellular phones which everyone can use and access it. Therefore, the pulse business has become one of the profitable and promising business opportunities for the future. This study aims to determine the implementation of financial records at the pulse counter and to determine the extent of the understanding of the CV. Mietha Global pulse counter entrepreneurs towards accounting. The research method used is descriptive qualitative research method which aims to determine and explain the implementation of financial records in pulse MSMEs. The results showed that entrepreneurs have been able to carry out financial records in accordance with their own knowledge and understanding. Entrepreneurs make financial records of their business according to their needs and abilities, this is done because they still think about how their business can survive and develop and can increase business income.